EXPLORING AN ACADEMIC WRITING CLASS IN AN INDONESIAN UNIVERSITY CONTEXT - Aunurrahman, Aunurrahman; Hamied, Fuad Abdul; Emilia, Emi (Language Circle: Journal of Language and Literature, 2016)
Academic writing class in any Indonesian university context plays an important role for the students to cope with written academic assignments. This paper explores the perceptions of university students regarding their academic writing class. The participants were students of a private university in Pontianak, West Kalimantan, Indonesia. They were selected based on their achievements in the class and their genders. The data collection made use of interviews which were conducted immediately after the completion of the class.Â  Individual interviews were conducted with six participants with three of them were male and the other three were female who were mainly regarded as medium achievers. The interview sessions were audio taped. The data then transcribed and analysed thematically. The discussion of the findings showed that the students gained benefits from the class through the applications of genre-based approach teaching stages, explicit teaching, and group work, which enabled the lecturer to develop the students academic writing, critical thinking, and characters. Still, several limitations were also identified. Suggestions were offered by the participants for the betterment of the academic writing class.